RANCANG BANGUN SISTEM PROTEKSI DAN MAPPING PEMADAMAN API PADA KEBAKARAN RUMAH - Hinfala, Bronsi; Paramytha, Nina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Detecting fires early so that mitigation actions can be taken more quickly, saving the lives of residents and protecting property from damage due to fire, and providing an automatic response to fire detection without the need for human intervention. This tool operates by utilizing technology with an Arduino Uno microcontroller as the processor in the system, along with a temperature sensor, flame sensor, and MQ2 sensor, as well as a buzzer as an alarm to indicate the occurrence of a fire and a DC pump controlled by the microcontroller to extinguish the fire when the sensors detect smoke and flames. These sensors have specific criteria that must be met for the device to become active. The research was conducted by simulating the equipment to test the temperature sensor, flame sensor, smoke sensor, and water pump to meet the specified criteria. The results showed that the fire protection system and mapping for extinguishing fires in residential areas were in accordance with the plan.Keywords: Arduino uno, Fire, Mapping, Microcontroller, Protection System